WILLOW LEAF SILAGE: EVALUATION OF QUALITY, ORGANOLEPTIC CHARACTERISTICS, ACCEPTABILITY, AND RUMEN DEGRADABILITY IN GOAT FEED - Steffen, Kevin Denis; Muro, María Gabriela; Trigo, María Soledad; Rodrigues, Matías Lucas; Cordiviola, Carlos Ángel; Arias, Rubén Omar (Chilean Journal of Agricultural & Animal Sciences, 2024)
This study aims to evaluate the nutritional composition, pH evolution, and organoleptic characteristics, acceptability, and rumen degradability of willow leaf silage intended for goat feeding. Leaves and edible stems of “Ragonese 131-27 INTA” willow (Salix babylonica x Salix alba) were collected, chopped and then ensiled for 84 days by chipping. Three different microsilages were evaluated: Willow leaf silage, willow leaf silage with 20% corn grain, and willow leaf silage with 20% wheat bran. The pH was measured, and a pH evolution curve was constructed for the different microsilages. The nutritional composition was evaluated in terms of dry matter, crude protein, neutral detergent fibre, acid detergent fibre, and organic matter. The organoleptic characteristics and acceptability test in goats were also determined. The willow leaf silage with 20% wheat bran recorded the best conservation and nutritional composition, and a better acceptance by goats with respect to the rest of the silages. Regarding rumen degradability, the willow leaf silage with 20% corn grain had the highest performance. Therefore, willow leaf silage constitutes a recommendable alternative feed for goats.